PENGARUH LINGKUNGAN KERJA, GAYA KEPEMIMPINAN, DAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA KANTOR BADAN KESATUAN BANGSA DAN POLITIK KABUPATEN SIDENRENG RAPPANG - Maryani Maryani; Ahmad Firman; Basri Rakhman (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
Abstract Maryani. 2022. The Effect of Work Environment, Leadership Style, and Motivation toward Employee Performance at the Office of the National Unity and Politics of Sidenreng Rappang Regency, supervised by Ahmad Firman and H. Basri Rakhman. This study aims to analyze (1) the effect of the work environment, leadership style, and motivation on employee performance at the Office of the National Unity and Politics of Sidrap Regency (2) the effect of the work environment, leadership style, and motivation on employee performance at the National Unity Agency Office and Politics of Sidrap Regency (3) the most dominant variable affects employee performance at the Office of the National Unity and Politics of Sidrap Regency. This research is a quantitative research with a survey method with correlational analysis techniques to determine the effect of the relationship between the dependent variable and the independent variable. Data collection methods used are questionnaires and document studies. The analytical method used is descriptive statistical analysis and multiple linear regression analysis. The results show that (1) partially the work environment variable had a dominant effect on employee performance (2) partially the leadership style variable had an effect on employee performance (3) partially the motivation variable had an effect on employee performance (4) partially and simultaneously the variables of work environment, leadership style and motivation have an effect on employee performance, which means that an increase in the work environment, leadership style and motivation will affect the performance of the Sidrap Regency Office of the National Unity and Political Office by 89.1%.